2015
DOI: 10.1590/1678-4499.0315
|View full text |Cite
|
Sign up to set email alerts
|

Análise dialélica e depressão endogâmica de híbridos forrageiros de milho para características agronômicas e de qualidade bromatológica

Abstract: This study aimed to estimate the combining ability and inbreeding depression of corn hybrids for agronomic traits and forage quality. Nine corn hybrids, 36 F1 combinations from a diallel, 9 S1 populations and two checks were evaluated in two experiments in a randomized complete block design with three replications, in the 2009/2010 and 2010/2011 growing seasons. The parents Impacto, CD304 and DKB390 are recommended to form a composite to be subjected to a recurrent selection program aiming to improve forage pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
(17 reference statements)
1
6
0
3
Order By: Relevance
“…This result was predictable given the importance of the non-additive genetic effects that control the inheritance of polygenic traits as well as the role of genic complementation in the heterotic expression observed in simple hybrids. The ID results obtained in the present study are consistent with the variation in ID in other studies of grain yield (BERNINI et al, 2013;SENHORINHO et al, 2015) and silage (SOUZA NETO et al, 2015).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result was predictable given the importance of the non-additive genetic effects that control the inheritance of polygenic traits as well as the role of genic complementation in the heterotic expression observed in simple hybrids. The ID results obtained in the present study are consistent with the variation in ID in other studies of grain yield (BERNINI et al, 2013;SENHORINHO et al, 2015) and silage (SOUZA NETO et al, 2015).…”
Section: Resultssupporting
confidence: 93%
“…Several authors support the efficacy of the expected pure inbred lines methodology, as well as inbreeding depression, in predicting the breeding potential of segregating populations based on maize forage quality, grain yield and popcorn quality (SCAPIM et al 2006;ARNHOLD et al, 2010;BERNINI et al, 2013;SOUZA NETO et al, 2015). However, there is no literature related to the deleterious effects of inbreeding depression on green corn production and quality characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…GY was assessed by measurement of the grain mass produced in each plot after discarding the cob and is expressed in kg•ha −1 . In order to adapt the measurement of the yield, it was carried out the stand correction method, by analysis of covariance between the number of plants per plot and GY, according to the covariance of ideal stand methodology, proposed by Vencovsky and Barriga (1992). PE was determined by means of a seed sample, taken from the basal center of the ears (Granate et al 2002) in each plot.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, diallel analysis is considered an important statistical tool for estimating parameters useful in selecting parents (Seifert et al 2006;Barreto et al 2012;Souza Neto et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ferreira et al (2008) found prevalence of non-additive effects for the character ear height in a partial diallel involving 24 single hybrids of maize. Souza Neto et al (2015) reported the existence of non-additive effects in assessing the diallel analysis of maize forage hybrids for agronomic and nutritive characteristics of maize.…”
Section: Resultsmentioning
confidence: 99%